PEMIKIRAN PROF. DR. ZAKIAH DARADJAT TENTANG PENDIDIKAN ISLAM(Analisis Terhadap Aspek Lingkungan Pendidikan Islam) - Hamida Olfah (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
Islamic education plays a large role in the life of individuals and society, especially in child development. With the current advances in science and technology, many children are carried away by the flow of globalization so that they behave in a deviant manner and even fall into criminal acts. For this reason, it is necessary to grow Islamic education in the family, school and community environment. Therefore, teachers need to introduce these three aspects. Many educational figures discuss children's education, one of which is Zakiah Daradjat. She is the only Indonesian female thinker who pays a lot of attention to various fields including the fields of education, morals, the lives of children, youth, teachers, family and schools. In this paper the author presents the concept of Islamic education according to Zakiah Daradjat's thoughts and how the environment influences the development of religious psychology in children and how its relevance to the goals of Islamic education. From this paper it can be concluded that (1) the concept of children's education in the family aspect of Zakiah Daradjat's perspective includes parents being role models for children, instilling the soul and piety given to children, (2) the concept of children's education in the school aspect of Zakiah Daradjat's perspective includes mental development , moral, religious education which is carried out intensively and talent then cultivates children's intelligence, (3) the concept of children's education in the social aspect of Zakiah Daradjat's perspective includes propagandizing things that degenerate children's morals and paying attention to children's associations and making places for guidance and counseling in children, and (4) the relevance of the concept of children's education in family aspects, school aspects and community aspects from Zakiah Daradjat's perspective with the aim of Islamic education, namely in the family aspect is the experience that children receive, in the school aspect is intelligence, while in the community aspect, namely educational attainment actually in the environment just society.